KOMPARASI PERSONAL BRANDING RIDWAN KAMIL: PEMILU WALIKOTA BANDUNG 2013 DAN PEMILU GUBERNUR JABAR 2018 - Puspita Yuli Pradita (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
Personal Branding is a form of a visual image carried out by individuals to gain public attention. One of the highlights is the personal branding displayed by Ridwan Kamil (RK) during the 2013 Mayor election campaign and also in the 2018 West Java Governor Election. There has been a change in the personal branding strategy carried out by Ridwan Kamil. It was seen that there was a political maneuver to gain the public trusts. This study examines the changes in Ridwan Kamil personal branding during that election. The value of the visual elements of RK personal branding becomes the basis of his behavioral. This study used qualitative methods, using FGD (Focus Group Discussion) analyzing visual social semiotics and also by literature study. This study revealed the changes in political maneuvers of Ridwan Kamil from nationalist and flexible to become more religious and conservative, shown by the graphics of his campaign elements. This related to his political mission and also from targeted election peers.